The Students' Learning Motivation in EFL Online Learning - Sri Nurfitri Amriyati; Kisman Salija; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2022)
This study was carried out at SMA 9 Makassar to determine students' learning motivation in EFL online learning. The goal of this study is to determine what students' intrinsic and extrinsic motivations are for online learning. The XII grade students of SMA N 9 Makassar are the focus of this study. In this study, data was gathered through observation, interviews, and documentation. According to the findings of this study, students' intrinsic motivation is caused by an internal desire to get good grades or a desire to receive something in the form of a gift in order to motivate these students to learn. The second finding is that healthy students' physical condition and senses make them more motivated. the most motivating thing from the extrinsic motivation of students was indeed guidance or encouragement, support from parents and family, the second is a supportive environmental factor, and interesting and not boring material.